Silent night eaudiobook - Steel, Danielle (Recorded Books Inc., 2019)
A shocking accident. A little girl struggling to survive. And the childless aunt who transforms her own world to help her ... Danielle Steel's latest novel is a deeply moving story of resilience and hope. Paige Watts is the ultimate stage mother. The daughter of Hollywood royalty, Paige channels her acting dreams into making her own daughter, Emma, a star. By the age of nine, Emma is playing a central role in a hit TV show. Then everything is shattered by unforeseeable tragedy. Now Emma is living with her aunt Whitney, who had chosen a very different path from her sister's. Whitney was always the studious older sister, hating the cult of celebrity that enveloped their childhood. Instead, she is a psychiatrist who lives for her work and enjoys a no-strings-attached love affair with a wealthy venture capitalist. But at a moment's notice, Whitney drops everything to help her niece. Once famous, outgoing, and charismatic, Emma is now a shadow of her former self—without speech, without memory, lost and terrified. But with her aunt Whitney's help, along with a team of caregivers and doctors, Emma begins to find her way, starting her young life all over again—and changing the lives of everyone around her. Emotionally gripping and richly involving, Silent Night explores how the heart has mysterious healing powers of its own, and blessings happen when we think all is lost.